KONSTELASI POLITIK DALAM NOVEL RORO JONGGRANG KARYA BUDI SARDJONO SEBUAH PENDEKATAN SOSIOLOGI SASTRA - Nukita Rachmawati; Rusdian Noor Dermawan (Universitas Sarjanawiyata Tamansiswa, 2017)
The aim of the study is to describe (1) plot of the story used by the writer to convey politics constellation in Roro Jonggrang novel, (2) character and characterization used by the writer to convey politics constellation in Roro Jonggrang novel, (3) background of the story used by the writer to convey politics constellation in Roro Jonggrang novel, and (4) politics constellation contained in Roro Jonggrang novel. The kind of this research is qualitative research. The data is phenomenon unit in Roro Jonggrang novel that accommodates plot, character, characterization, background, and constellation politics. The source of the data is a novel entitled Roro Jonggrang by Budi Sardjono. The instrument of the research is the researcher that has given a theory about the plot, background, character, characterization, background, and constellation politics, especially sociological politics. the technique of collecting data are observation, reading technique, and taking a note. The technique of data analysis is descriptive qualitative technique. The result of this study is as follows. (1) The plot used in Roro Jonggrang novel is a chronological plot. (2) The main character is Roro Jonggrang, beside that there is another character as an addition. (3) Background of the study happens in Gedono temple, Prambanan temple, Suruh Ijo village, Kalibawang village, Kaswargan hill, Pengging square, Cepogo temple, dan Ciwa temple. The time of the story is described in the ninth century when mataram kingdom holds the power. The events are taken during morning, afternoon and evening time. social background in this novel is society and Javanese culture. (4) Politics constellation in this novel is:Â (a) Politics communication happens between Pengging and Prambanan kingdom. In pengging kingdom, politics communication is done by Prabu Damar Maya, Bandung Bandawasa, Demang Selo, Demang Tegalrejo, Lurah prajurit Pengging, and Tumenggung Gagak Sabrang, whereas in prambanan kingdom politics communication is done by Roro Jonggrang, Dyah Mranti, Lurah Berbah, Lurah Kretek, and Prabu Baka Geni. In this politics communication, there are some functions done by each kingdom. the function of politics communication is information function, instruction function, and persuasive function. (b) Politics participation happens between Pengging and Prambanan kingdom. Politics participation in pengging kingdom is marked by the participation of group soldier of Adipati Wono Goro, Loda Nyang, and Pengging soldier, whereas politics participation in Prambanan kingdom is marked by village chief participation. (c) There are two social movements in Roro Jonggrang novel. They are regressive and expressive movement. Each kingdom did both of the movement.Â